Introduction of Pack Test for Participative Environmental Monitoring and Environmental Education for Sustainability in Malaysia - Muhammad Faiz Bin Abd Rahman (Journal of Tropical Life Science, 2011)
Pack Test which provided by Kyoritsu Chemical-Check Lab. Corporation has been assumed as a professional easy-to-use onsite water quality checker. The aim of this study is to examine the possibility of application of Pack Test in Malaysia, and to assess the required matters during introduction processes. Two workshops were sampled to prove the potential function of Pack Test in environmental education and participative environmental monitoring. Two hours lecture of Universiti Teknologi Malaysia (UTM) was facilitated as a workshop by author on September 23, 2010, and then the author has assisted a workshop in Putrajaya on October 9, 2010. Questionnaire forms were applied to test as if peoples feeling are positive or not towards Pack Test as preliminary research. Water quality parameters were simultaneously measured by Pack Test, such as, COD, NO3-, CI-, and NH4+ in UTM, pH and NO3- were measured in Putrajaya workshop, respectively. Participant’s feeling in the both workshops showed strong positive potential for Pack Test. Results of water qualities from UTM workshop had big variation in COD and NO3-. Considering the reason, the UTM workshop was conducted without proper support for both facilitator and participant. Participants were able to classify the water quality level in a short time. As for the Putrajaya workshop, with deep support and well skilled instruction by facilitator team, the data showed small variation i.e. good and consistent water quality result. It was obvious that Pack Test was always applicable to assess water environment and it was well functioned as user friendly easy-to-use water quality checker. Thereby the role of Pack Test was segregated from conventional standard methods. The participant’s feeling to Pack Test was strong positive for implementation and to improve public environmental awareness. Simultaneously, they were feeling that peoples can participate more effectively in water environment issues by Pack Test. It was clear that Pack Test was notable in-situ water quality checker, which has advantages over its particular methods that never rely on transport of samples to a distant laboratory for chemical analysis. Above all, it could be a breakthrough point to empower public participation, and environmental education for water sustainability. In addition, it can be pointed out that if there are chance to get skilled of the usage of Pack Test, which will be important for teachers, engineers, and other potential facilitators to ensure the effective usage of Pack Test towards.Keywords: Environmental awareness,Public participation, Simplify environmental monitoring tool, Strategic environmental assessment, Water quality